The Municipal Register Containing the City Charter and Ordinances, Together with the Rules and Orders of the City Council and a List of the past and Present City Officers of the City of Newburyport at 130, Ordinance No. 14, An Ordinance for the Prevention of Certain acts in the Streets and on the Public Grounds of the City § 15 (1869) - (:unkn) unknown (General Publisher, 1869)
No person shall fire any rocket, squib, cracker, or other thing formed of gunpowder or other explosive substance, in whole or in part; nor make any bonfire of tar barrels or any other substances, nor, except in the performance of some duty authorized by law, discharge any field piece, gun or other firearm in or upon any street or other way, or upon any wharf or landing within the city.
--
Keywords: DISCHARGE